Factors affecting sustainability of financing Technical and Vocational Education and Training in Kenya - Mutua, Vivianne (Strathmore University, 2021)
Technical and Vocational Education and Training (TVET) is an essential element of Skill management and has a fundamental part to play in achieving sustainable development. The purpose of this study is to determine the factors affecting sustainability of financing of TVET in Kenya. The study was conducted in the Higher Education Loans Board since it is the body that grants loans to TVET institutions. The objectives of the study were to determine the effect of financing policy and regulations, financial diversity, employability of graduates and graduates’ attitudes towards government loans on the sustainability of financing of TVET in Kenya. The study used a descriptive research design, and the population of interest was 113 employees. Stratified random sampling was used to come up with 88 respondents. The research predominantly utilized primary data in form of questionnaires. Secondary data in form of reports and publications was also utilized. The questionnaires comprised of both close and open-ended questions. Descriptive statistics was employed in the analysis of data while regression analysis was employed in establishing the relationship amongst the studied variables. The findings show that there existed a moderate positive relationship between financing policy and regulations on sustainability of financing and there was accountability of the funds allocated to TVET programmes, compliance with financial policy and regulations governing the award of TVET loans. There was a positive relationship between financial diversity on sustainability of financing of TVET and there was a higher dependence on government own funding to fund TVET programmes. There was a positive relationship between employability of graduates on sustainability of financing of TVET and the inability to pay due to unemployment is a major factor that affects TVET programmes sustainability. Graduates’ attitudes towards government loans has a positive influence on sustainability of financing of TVET in Kenya and future earnings of graduate students influence TVET loans repayment. The study recommends that the government through HELB should review the policy on penalties levied on defaulters to control how and when penalties are charged to curb ever rising loan default. The policy should provide framework to protect unemployed undergraduate beneficiaries from being charged penalties until when they secure employment. The study also recommends that HELB should introduce a reward scheme for those who finish paying their loan on record time; this will instill motivation towards repayment of HELB loan in Kenya. The study recommends that HELB should escalate on their seminars and sensitization forums to sensitize graduates to repay their loans.
Submitted in partial fulfilment of the requirements for the degree of Master of Public Policy and Management at Strathmore University
Keywords: Sustainability of financing; Financing policy; Financial diversity; Employability of graduates